2021
DOI: 10.1055/a-1659-6214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Role of Integrin α5β1 in Platelet Function, Hemostasis, and Experimental Thrombosis

Abstract: Objective: Integrins are key regulators of various platelet functions. The pathophysiological importance of most platelet integrins has been investigated, with the exception of α5β1, a receptor for fibronectin. The aim of this study was to characterize the role of α5β1 in megakaryopoiesis, platelet function, and to determine its importance in hemostasis and arterial thrombosis. Approach and results: We generated a mouse strain deficient for integrin α5β1 on megakaryocytes and platelets (PF4Cre-α5-/-). PF4Cre-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We recently reported that α5β1 does not seem to play a major role in arterial thrombosis as PF4Cre-α5 -/- mice did not display reduced thrombosis in three different in vivo models (ferric chloride injury of the carotid artery, mechanical lesion of the abdominal aorta and laser lesion of mesenteric arterioles). 35 Concerning α6β1, our group observed that PF4Cre-α6 -/- mice are protected against thrombosis in in vivo models using a mechanical or laser lesion. 36 This protection reached the same level as in the PF4Cre-β1 -/- mice mentioned above, 36 suggesting that the platelet β1 integrin with greatest importance in arterial thrombosis is α6β1.…”
Section: The Importance Of Platelet Integrins In Arterial Thrombosismentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that α5β1 does not seem to play a major role in arterial thrombosis as PF4Cre-α5 -/- mice did not display reduced thrombosis in three different in vivo models (ferric chloride injury of the carotid artery, mechanical lesion of the abdominal aorta and laser lesion of mesenteric arterioles). 35 Concerning α6β1, our group observed that PF4Cre-α6 -/- mice are protected against thrombosis in in vivo models using a mechanical or laser lesion. 36 This protection reached the same level as in the PF4Cre-β1 -/- mice mentioned above, 36 suggesting that the platelet β1 integrin with greatest importance in arterial thrombosis is α6β1.…”
Section: The Importance Of Platelet Integrins In Arterial Thrombosismentioning
confidence: 99%
“…Indeed, perfusion of whole blood from mice genetically deficient in α5 in the platelet linage (PF4Cre-α5 -/- ) over collagen, a surface that does not activate α5β1, resulted in a reduced thrombus volume as compared to that following perfusion of whole blood from control mice. 35 This suggests that α5β1 contributes to thrombus formation through an interaction with plasma fibronectin. However, the same effect was not observed using human blood perfused over collagen in the presence of an anti-α5 blocking antibody.…”
Section: The Role Of Integrins In the Formation Of A Hemostatic Plugmentioning
confidence: 99%
See 1 more Smart Citation
“…The most abundant and best-characterized integrin is αIIbβ3 [58]. Recently, the importance of α5β1 in hemostasis under normal and inflammatory conditions has also been better defined [59]. Various agonists may modulate the affinity of integrins for their ligands, thereby reinforcing platelet activation [57].…”
Section: Mirnome Modulation Upon Platelet Activationmentioning
confidence: 99%
“…We and others identified a role for integrin α5β1 in platelet adhesion, activation and aggregation on fibronectin in vitro . In FeCl 3 -, forceps- and laser-injury models of arterial thrombosis, mice invalidated for the platelet α5β1 present a normal profile of thrombus formation [ 3 ]. Furthermore, the normal tail-bleeding time favors no major role of this integrin in hemostasis.…”
Section: Role Of Integrin α5β1 In Platelet Function Haemostasis and A...mentioning
confidence: 99%